Gamification Adoption in Higher Education: TechFit Acceptance Model - Lasambau, Carolina Magdalena; Juniarti, Cahaya; Nuryati, Neneng; Yuliyawati, Sri Nur; Milanti, Ajeng Ayu (Media Komunikasi FPIPS, 2025)
This study explores the factors influencing individuals' intention to continue using gamification applications in learning, utilizing the Technology Acceptance Model (TAM) and Technology-Task Fit (TTF). Data were collected through a survey of 304 respondents using gamified learning in Indonesia. Structural Equation Modeling-Partial Least Square (SEM-PLS) was conducted to analyze the relationships between variables and test a series of hypotheses. Then, it was analyzed using Importance-Performance Map Analysis (IPMA). Using SEM-PLS and IPMA, the findings revealed that TTF constructs influence perceived usefulness (PU) and perceived ease of use (PEOU), except for technology characteristics, which do not significantly impact PEOU. Additionally, attitude is influenced by the two main TAM variables: PU and PEOU. The continuance intention to adopt gamification is influenced by attitude. This study will assist educators, educational institutions, gamification application developers, policymakers, and others concerned with the future development of education in designing effective strategies to enhance the adoption of gamification in learning. This study is the first to empirically employ the TAM and TTF to analyze the adoption of gamification applications in higher education.